Development of propolis and essential oils containing oral/throat spray formulation against SARS-CoV-2 infection. (October 2022) - Pelvan, Ebru; Serhatlı, Müge; Karaoğlu, Öznur; Karadeniz, Bülent; Pembeci Kodolbaş, Ceyda; Aslı Öncü, Neşe; Çakırca, Gamze; Damarlı, Emel; Başdoğan, Günay; Mergen Duymaz, Gizem; Emir Akyıldız, İsmail and Düz, Gamze and Acar, Sezer and Özhan, Yağmur and Sipahi, Hande and Charehsaz, Mohammad and Aydın, Ahmet and Yesilada, Erdem and Alasalvar, Cesarettin
Graphical abstract: Highlights: An oral/throat spray formulation for prophylactic use was developed. Forty-three phenolics were identified in both propolis and oral/throat spray. The spray with 1:640-fold dilution provided the highest efficacy. The spray can be used as a supplement for the prevention of SARS-CoV-2 infection. Abstract: A broad range of evidence has confirmed that natural products and essential oils might have the potential to suppress COVID-19 infection. Therefore, this study aimed to develop an oral/throat spray formulation for prophylactic use in the oral cavity or help treatment modalities. Based on a reference survey, several essential oils, a cold-pressed oil, and propolis were selected, and cytotoxicity and antiviral activity of each component and the developed spray formulation were examined against severe acute respiratory syndrome coronavirus-2 (SARS-CoV-2) infection using Vero E6 cells. Anti-inflammatory, antimicrobial, and analgesic activities as well as mutagenicity and anti-mutagenicity of the formulation were analysed. Forty-three phenolics were identified in both propolis extract and oral/throat spray. The spray with 1:640-fold dilution provided the highest efficacy and the cytopathic effect was delayed for 54 h at this dilution, and the antiviral activity rate was 85.3%. A combination of natural products with essential oils at the right concentrations can be used as a supplement for the prevention of SARS-CoV-2 infection.